Amelioration of Colitis in Mouse Model by Exploring Antioxidative Potentials of an Indigenous Probiotic Strain of Lactobacillus fermentum Lf1. (1st July 2014) - Chauhan, Ritu; Sudhakaran Vasanthakumari, Aparna; Panwar, Harsh; Mallapa, Rashmi H.; Duary, Raj Kumar; Batish, Virender Kumar; Grover, Sunita
Abstract : Based on the preliminary screening of eight indigenous putative probiotic Lactobacilli, Lactobacillus fermentum Lf1 was selected for assessing its antioxidative efficacy in DSS colitis mouse model based on its ability to enhance the expression of " Nrf 2" by 6.43-fold and malondialdehyde (MDA) inhibition by 78.1 ± 0.24% in HT-29 cells under H2 O2 stress. The Disease Activity Index and histological scores of Lf1-treated mice were lower than the control group. However, expression of " Nrf 2" was not observed in Lf1-treated mice. A significant increase in the expression of antioxidative enzymes such as SOD 2 and TrxR -1 was recorded in both of the groups. The expression of SOD 2 was significantly downregulated in colitis-induced mice by −100.00-fold relative to control group, and the downregulation was considerably reduced to −37.04-fold in colitis Lf1 treatment group. Almost, a similar trend was recorded in case of "thioredoxin" expression, though "CAT" was refractile to expression. The Lf1-treated group had decreased malondialdehyde level as compared to colitis control (37.92 ± 6.31 versus 91.13 ± 5.76 μ M/g). These results point towards Lf1-induced activation of the antioxidant enzyme system in the mouse model and its prospects to be explored as a new strategy for IBD management.